Assessment of Service Quality on Public Satisfaction in Motor Vehicle Testing: A Study of the Transportation Department in Paser Regency - Idris, Muhammad; Geraldina, Ira; Gunarto, Muji (International Journal of Business, Management and Economics, 2024)
In an increasingly competitive era of public service, understanding the factors that influence public satisfaction is crucial for enhancing service quality. The primary objective of this study is to identify and analyze the impact of five service quality dimensions—tangibles, reliability, responsiveness, assurance, and empathy—on public satisfaction. This research also aims to provide recommendations for improving service quality at the Department of Transportation in Paser Regency. The study employs a quantitative approach using a survey method. Data were collected from 60 respondents who had used motor vehicle testing services within the last six months. Purposive sampling was employed to determine the sample, and data were gathered through questionnaires adapted from the SERVQUAL instrument. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships between variables. The findings indicate that of the five service quality dimensions tested, only assurance and empathy have a positive and significant impact on public satisfaction. Assurance was the most dominant factor, highlighting that the knowledge and competence of staff in providing safe and reliable services are crucial to the public. Empathy also plays a significant role, as attention and understanding of individual needs enhance satisfaction. Conversely, the dimensions of tangibles, reliability, and responsiveness did not show a significant impact on public satisfaction, suggesting that other factors might be more influential in this context. The managerial implications of these findings include the need for improvements in supporting facilities, regular training for staff, increased responsiveness, and the development of empathetic attitudes. With these measures, it is expected that service quality can be significantly improved, ultimately enhancing public satisfaction.